Chiari Formation: Atlantoaxial Instability is the Cause - Atul Goel (Iranian Journal of Neurosurgery, 2017)
The entity of Chiari formation was described by Hans Chiari in 1891 [1,2]. Since then the subject has been evaluated elaborately by a number of authors. However, it may only be correct to state that confusion in the understanding of pathogenesis and the nature of anomaly, significance of associated  abnormal soft tissue and bone anomalies and more importantly the treatment of the entity has not been resolved. The number of described treatment patterns are a testimony to the inadequacy of the understanding. The general consensus is that uncal herniation and tonsillar herniation are both similar in their pathogenesis wherein the part of the temporal brain or the cerebellum are pushed out of their compartment through a hiatus or hole into the other body compartment. In the process of herniation, there is congestion of space and compromise of the neural structures in the vicinity that leads to neurological symptoms or deficits. The factor that causes the push in case of Chiari malformation is unclear. However, the presence of an increased volume of cerebellar mass, a smaller volume of the posterior cranial fossa bone compartment or a combination of both these factors could be the possible cause. The general understanding is that the addition of the tonsillar volume in the foramen magnum limits the space for the neural structures that are compressed and results in related symptoms. Foramen magnum decompression is an established and a gold standard form of treatment.